2008
DOI: 10.1136/ard.2008.092791
|View full text |Cite
|
Sign up to set email alerts
|

Residual inflammation after rituximab treatment is associated with sustained synovial plasma cell infiltration and enhanced B cell repopulation

Abstract: The present study demonstrated that a low disease activity state following rituximab was associated with reduced infiltration of CD79a+ CD20- plasma cells in synovium and reduced B cell repopulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 25 publications
3
51
0
2
Order By: Relevance
“…Rituximab leads to transient but almost complete depletion of B cells in the blood and only partial depletion in the bone marrow813 and synovial tissue 1416. Response has been shown to correlate with the level of synovial membrane B-cell depletion9 and early peripheral blood depletion of B cells measured by sensitive assays,9 possibly useful as a surrogate.…”
Section: Mechanism Of Action Of Rituximab In Ramentioning
confidence: 99%
“…Rituximab leads to transient but almost complete depletion of B cells in the blood and only partial depletion in the bone marrow813 and synovial tissue 1416. Response has been shown to correlate with the level of synovial membrane B-cell depletion9 and early peripheral blood depletion of B cells measured by sensitive assays,9 possibly useful as a surrogate.…”
Section: Mechanism Of Action Of Rituximab In Ramentioning
confidence: 99%
“…28,29 This is further underscored by the presence of B cells in the joints and salivary glands of patients with rheumatoid arthritis and Sjögren's syndrome, respectively, sites that are also resistant to depletion by RTX. 30,31 These B cells may eventually die and not be replenished because of systemic depletion, thus explaining the delay in the effect of RTX.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, an in vitro non-depleting study also demonstrated a better efficacy of rituximab on CD27 -naive B-cells compared to CD27 + memory B regarding B-cell activation, proliferation, and viability [107]. Few months after the first injection of rituximab, transitional B-cells repopulation is observed and plasma cells recirculate in the peripheral blood of treated patients [108,109]. Moreover, notably in rheumatoid arthritis patients, a high proportion of circulating memory B-cells is associated with increased risk of relapse in patients receiving rituximab [108,110].…”
Section: Rituximabmentioning
confidence: 93%